2022
DOI: 10.2147/vmrr.s347373
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Associated Risk Factors of Infectious Bursal Disease in Chickens Managed Under Intensive and Backyard Production Systems in Western Oromia, Ethiopia

Abstract: Background Infectious bursal disease (IBD) is a highly contagious viral disease challenging poultry industry throughout the world. It is also among the main obstacles in the different chicken production system in Ethiopia. This study was conducted with the aim of determining seroprevalence and associated risk factors of IBD in backyard and intensively managed chickens of the study area. Methods A cross-sectional study was conducted in selected districts of western Oromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(21 reference statements)
1
3
1
Order By: Relevance
“…According to the rearing system, there was no significant difference in incidence of IBD between opened (75.8%) and closed systems (75.9%). This is not similar to previous studies, which reported that the IBD incidence increased in chickens housed in opened system due to frequent exposure to immunosuppressive factors such as heat stress, deprivation of water, and poor nutrition which resulted in suppression of the chicken immune system [49,50].…”
Section: Discussioncontrasting
confidence: 93%
“…According to the rearing system, there was no significant difference in incidence of IBD between opened (75.8%) and closed systems (75.9%). This is not similar to previous studies, which reported that the IBD incidence increased in chickens housed in opened system due to frequent exposure to immunosuppressive factors such as heat stress, deprivation of water, and poor nutrition which resulted in suppression of the chicken immune system [49,50].…”
Section: Discussioncontrasting
confidence: 93%
“…Our current findings were similar to those of previous studies conducted globally, for example, 86% by Bolfa et al [34] in St. Kitts, 83.1% by Jenbreie et al [35], and 83% by Tadesse and Jenbere [20] in Ethiopia. Converse findings were also recorded by different earlier studies; for example, a higher prevalence was detected by Chaka et al [36] in Ethiopia with 91.9% seropositivity; lower prevalence was determined by Jordan et al [37] in Trinidad and Tobago, Abdeta et al [38] in Western Ethiopia, and Lemma et al [39] in Eastern Ethiopia with 67.5%, 66.93%, and 51.7% seropositive rates of IBDV antibodies, respectively. Disparities in several risk factors, such as geographical distribution, sample size, sample collection procedure, sample processing system, and sensitivity and specificity of the detection tools, could lead to significant variations between the current study and earlier investigations.…”
Section: Discussionsupporting
confidence: 56%
“…Poor farm hygiene, biosecurity, age of the flock, insufficient vaccine coverage, production type (closed or open houses), floor type, flock size, farmers' education, and know-how are directly linked with commonly occurring poultry diseases (Carrique-Mas et al, 2019;Islam et al 2021). Abdeta et al (2022) also used indirect ELISA to detect the seroprevalence of IBD in backyard poultry in Ethiopia. They found 66.93% positive samples.…”
Section: Resultsmentioning
confidence: 99%